Alantolactone selectively ablates acute myeloid leukemia stem and progenitor cells. Issue 1 (December 2016) - Ding, Yahui; Gao, Huier; Zhang, Yu; Li, Ye; Vasdev, Neil; Gao, Yingdai; Chen, Yue; Zhang, Quan
Abstract Background The poor outcomes for patients diagnosed with acute myeloid leukemia (AML) are largely attributed to leukemia stem cells (LSCs) which are difficult to eliminate with conventional therapy and responsible for relapse. Thus, new therapeutic strategies which could selectively target LSCs in clinical leukemia treatment and avoid drug resistance are urgently needed. However, only a few small molecules have been reported to show anti-LSCs activity. Methods The aim of the present study was to identify alantolactone as novel agent that can ablate acute myeloid leukemia stem and progenitor cells from AML patient specimens and evaluate the anticancer activity of alantolactone in vitro and in vivo. Results The present study is the first to demonstrate that alantolactone, a prominent eudesmane-type sesquiterpene lactone, could specifically ablate LSCs from AML patient specimens. Furthermore, in comparison to the conventional chemotherapy drug, cytosine arabinoside (Ara-C), alantolactone showed superior effects of leukemia cytotoxicity while sparing normal hematopoietic cells. Alantolactone induced apoptosis with a dose-dependent manner by suppression of NF-kB and its downstream target proteins. DMA-alantolactone, a water-soluble prodrug of alantolactone, could suppress tumor growth in vivo. Conclusions Based on these results, we propose that alantolactone may represent a novel LSCs-targeted therapy and eudesmane-type sesquiterpene lactones offer a new scaffold for drug discovery towards anti-LSCs agents.